TINDAK TUTUR ILOKUSI EKSPRESIF DALAM VIDEO YOUTUBE “THE SHOCKING DIFFERENCE BETWEEN INDONESIAN AND KOREAN BATHING CULTURE”: KAJIAN PRAGMATIK LINTAS BUDAYA - Reisa Nurul Fauziya (Politeknik Negeri Jakarta, 2023)
Language is an example of a characteristic form of a country. This is because a language will reflect the culture of a country, so if you are studying a language, the culture behind that language must also be studied. Analyzed with expressive speech act theory from Searle (1969), this research focuses on the expressive speech acts used by Rosa, who is a South Korean citizen who has lived in Indonesia for a long time, and Amelia Tantono and Adelyn Yunita, who are Indonesian citizens who have lived in South Korea for a long time in the video “The Shocking Difference Between Indonesian And Korean Bathing Culture” which was uploaded by the Rosakis YouTube channel. This study aims to identify the dominant expressive speech acts used by the three people in discussing the same topic through a cross-cultural pragmatic perspective. This study used a descriptive qualitative method. The results of the study show that expressive speech acts of lamentation and acceptance are the two dominant types of speech acts used because if an individual lives in a country that is not his origin, he will go through a phase of lamentation and finally a phase of acceptance of the culture that occurs in the country he lives in.